2016
DOI: 10.1007/s10195-016-0410-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of two percutaneous pinning techniques (lateral vs medial–lateral) for Gartland type III pediatric supracondylar fracture of the humerus

Abstract: BackgroundThe management of displaced supracondylar fracture of the humerus with closed reduction and percutaneous pin fixation is the most widely accepted method of treatment, but controversy continues regarding the pin fixation techniques. A prospective randomized controlled study was undertaken to compare the stability, functional outcome and iatrogenic ulnar nerve injury between lateral pin fixation and medial–lateral pin fixation.Material and methodSixty-two patients with Gartland type III supracondylar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 24 publications
3
53
1
6
Order By: Relevance
“…Pre-operative nerve injuries occur most commonly in older children. 3,4,14 We observed an overall incidence of 18.4% (seven children) of nerve injuries and the mean age for these children was 10 years, which confirmed the findings in the literature. Other studies in the literature have reported results within the same range.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Pre-operative nerve injuries occur most commonly in older children. 3,4,14 We observed an overall incidence of 18.4% (seven children) of nerve injuries and the mean age for these children was 10 years, which confirmed the findings in the literature. Other studies in the literature have reported results within the same range.…”
Section: Discussionsupporting
confidence: 87%
“…In terms of nerve injuries associated with extension-type supracondylar fractures, the most commonly injured nerve is the radial nerve followed by the median nerve and ulnar nerve. 3,4,14 In the current study the most commonly injured nerve was the ulnar nerve (excluding iatrogenic injuries) and then the radial nerve. The ulnar nerve injury is one of the most common iatrogenic complications recorded when using the crossed-pinning technique.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Cross pins and divergent lateral pins are said to have comparable stiffness in numerous clinical and biomechanical studies [8,9]. Many authors have however advocated for the lateral-only pins due to the risk of ulnar nerve injury with medially placed pins [10,11]. However, the use of cross pins may be inevitable in some cases, such as in medially oblique fractures, high fractures or fractures with medial comminution, which may have a higher incidence of loss of reduction in clinical practice [5].…”
Section: Introductionmentioning
confidence: 99%